Protective immune mechanisms against Theileria parva: Evolution of vaccine development strategies - McKeever, Declan J.; Taracha, E.L.N.; Morrison, W. Ivan; Musoke, A.J.; Morzaria, S.P. (Elsevier, 1999)
Theileria parva is an intracellular sporozoan parasite that infects and transforms bovine lymphocytes, causing a severe lymphoproliferative disease known as East Coast fever in eastern, central and southern Africa. In this article, Declan McKeever and colleagues summarize the current understanding of immune mechanisms provoked by the parasite with regard to their role in both pathogenesis and protection. In particular, the influence of genomic polymorphism in parasite and host on the development of immunity is discussed, along with the evolution of current vaccine development strategies as a result of immunological research on the disease.